2006
DOI: 10.1182/blood.v108.11.4820.4820
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Drug Monitoring of Imatinib and Impact on Clinical Decision Making.

Abstract: OBJECTIVES: Imatinib (IM) has demonstrated durable clinical efficacy in the majority of chronic myeloid leukemia (CML) patients. Optimal response may be influenced by multiple innate and external factors, some of which may be controlled by monitoring plasma concentrations of the drug. This abstract reports 6 cases where analyzing plasma IM trough concentrations (Cmin) in patients treated with three commonly used IM doses (400, 600, and 800 mg daily) influenced clinical decision making. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…These results are in agreement with those of other studies that found that IMPLs are a good predictor of clinical responses to therapy . Our results indicating that attaining a threshold of 1000 ng/mL of imatinib in plasma correlates with the achievement of an optimal CyR is analogous with the 1009 ng/mL threshold reported by Larson et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in agreement with those of other studies that found that IMPLs are a good predictor of clinical responses to therapy . Our results indicating that attaining a threshold of 1000 ng/mL of imatinib in plasma correlates with the achievement of an optimal CyR is analogous with the 1009 ng/mL threshold reported by Larson et al .…”
Section: Discussionsupporting
confidence: 93%
“…Although mechanisms of resistance, such as BCR‐ABL mutations , have been reported, the varying levels in patients' response to imatinib therapy may also be due to factors such as lack of adherence to therapy , pharmacokinetic differences , different levels of expression of cellular efflux/influx proteins , drug–drug interactions or absorption differences arising from gastrointestinal abnormalities or disease states . Previous reports from large multi‐international studies have demonstrated that monitoring of imatinib plasma trough levels correlates with both clinical responses and tolerability to therapy and may be useful for the management of patients with CML . Patients with a steady‐state C min of approximately 1000 ng/mL were more likely to reach therapeutic milestones, such as CCyR and MMR.…”
Section: Introductionmentioning
confidence: 99%
“…Our model also factored the two relationships—the effect of TDM on the plasma concentration of IM and the effect of the plasma concentration on therapeutic success of IM—in, and test the sensitivity of the conclusion against the changes in those factors. [20] (Fig 2).…”
Section: Methodsmentioning
confidence: 99%